Effects of Poor Subjective Sleep Quality on Symptoms of Depression and Anxiety among Adolescents - Kristín Gunnarsdóttir 1986- (2014)
Poor quality of sleep over a long period of time and shorter sleep duration have various negative effects on individual’s mental and physical health. The aim of this study was to examine the relationship between poor quality of sleep and increased symptoms of depression and anxiety among adolescents in Iceland and whether this relationship varies with gender. The study also examined the effect of adolescents’ sleep duration on same terms. Earlier findings have implied that poor quality of sleep along with short sleep duration is to correlate with high negative and low positive emotions. Studies have also implied that there is a gender difference in adolescent mental health but few studies have examined and compared these factors with sleep habits among adolescents. The current study used data from an ongoing research, Effects of exercise on well-being and quality of life among college students. The sample size was a total of 240 Icelandic first-year students from three different collages in the capital region. The sample contained 83 boys (36%) and 148 girls (64%). The current study explored the first part of the research. The data was collected via self-report where participants valued subjective quality of sleep and sleep duration as well as their mental health for the last 3 weeks. The results showed a significant main effect of poor quality of sleep and gender along with increased symptoms of anxiety and depression. However, no relation between sleep duration and gender was found. The results support previous findings that poor subjective quality of sleep can increase effects on deprivation and anxiety. The poorer the quality of sleep, the more symptoms of depression and anxiety were found among the adolescents. Keywords: quality of sleep, adolescence, well-being, quality of life, depression and anxiety Svefn hefur mikið verið rannsakaður í gegnum tíðina. Skortur á svefni og léleg gæði nætursvefns hafa verið tengd við neikvæð áhrif hugrænnar getu, hreyfingar og neikvæðra tilfinninga. Markmið ...